Preliminary X-ray crystallographic studies of BthTX-II, a myotoxic Asp49-phospholipase A(2) with low catalytic activity from Bothrops jararacussu venom - Correa, L. C.; Marchi-Salvador, D. P.; Cintra, A. C. O.; Soares, A. M.; Fontes, M. R. M. (Blackwell Publishing, 2006)
For the first time, a complete X-ray diffraction data set has been collected from a myotoxic Asp49-phospholipase A(2) (Asp49-PLA(2)) with low catalytic activity (BthTX-II from Bothrops jararacussu venom) and a molecular-replacement solution has been obtained with a dimer in the asymmetric unit. The quaternary structure of BthTX-II resembles the myotoxin Asp49-PLA(2) PrTX-III (piratoxin III from B. pirajai venom) and all non-catalytic and myotoxic dimeric Lys49-PLA(2)s. In contrast, the oligomeric structure of BthTX-II is different from the highly catalytic and non-myotoxic BthA-I (acidic PLA(2) from B. jararacussu). Thus, comparison between these structures should add insight into the catalytic and myotoxic activities of bothropic PLA(2)s.